2017
DOI: 10.1021/acs.cgd.7b00553
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Resolved Spectroscopic Study Reveals the Conversion Mechanism of CaO·Al2O3·10H2O to 2CaO·Al2O3·8H2O and 3CaO·Al2O3·6H2O at an Elevated Temperature

Abstract: The main binding phases of calcium aluminate cement (CAC) concrete, CaO•Al 2 O 3 •10H 2 O (CAH 10) and 2CaO•Al 2 O 3 •8H 2 O (C 2 AH 8), slowly convert to 3CaO•Al 2 O 3 • 6H 2 O (C 3 AH 6) and Al(OH) 3 (AH 3). This reaction significantly speeds up at a temperature higher than ∼30°C, and over time leads to significant strength loss in CAC concrete. Because of the lack of direct evidence that simultaneously probes morphological and chemical/crystallographic information, intense debate remains whether the convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 32 publications
(106 reference statements)
1
17
0
Order By: Relevance
“…In all of the investigated pastes (CCC, synthetic CA/CA 2 , synthetic CA 2 ) C 2 AH 8 formation and dehydration to C 2 AH 7.5 occurred prior to the formation of C 3 AH 6 . This sequence is in accordance with the works by Rashid et al and Geng et al . Whereas the two latter references concerned the conversion of CAH 10 , Rashid and Turrillas reported the intermediate formation of C 2 AH 8 prior to the formation of C 3 AH 6 also for the hydration of freshly prepared pastes of CA for temperatures up to 90°C.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In all of the investigated pastes (CCC, synthetic CA/CA 2 , synthetic CA 2 ) C 2 AH 8 formation and dehydration to C 2 AH 7.5 occurred prior to the formation of C 3 AH 6 . This sequence is in accordance with the works by Rashid et al and Geng et al . Whereas the two latter references concerned the conversion of CAH 10 , Rashid and Turrillas reported the intermediate formation of C 2 AH 8 prior to the formation of C 3 AH 6 also for the hydration of freshly prepared pastes of CA for temperatures up to 90°C.…”
Section: Discussionsupporting
confidence: 92%
“…This indicates that the C 2 AH x formation prior to the C 3 AH 6 formation would also occur in well‐sealed samples. Although the C 2 AH 8 is supposed to dissolve before C 3 AH 6 starts to precipitate the intermediate formation of C 2 AH 8 , nevertheless, seems to be essential for the C 3 AH 6 formation. Geng et al suggested that relics of dissolved C 2 AH 8 provide nucleation sites for C 3 AH 6 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations